Book of proceedings , international conference on environmental studies and research - Cabellero Luis; Chukwu Frank; Guerrero Christophe; Kosu Joseph; Olorode Yemisi; Archibong Florence; Connolly Dominic; Alexis Prince; Nosike Austin N.; Beverly Scientific Organisation (BSO)
La serie ICESR (International Conference on Environmental Studies and Research) es una actividad acadm̌ica cuyo props̤ito es difundir hallazgos investigativos y servir como m̀bito de debate e intercambio de ideas en el campo de las ciencias ambientales. Algunas de las ponencias presentadas son las siguientes (la lista completa se encuentra en la tabla de contenido del documento):Effective Environmental Management: A Panacea for Socio-economic Development of Developing CountriesTowards Mitigating the Impacts of Climate Change on Food Security: A Global PerspectiveGreenhouse Gases, Climate Change and Environmental Conservation for Sustainable DevelopmentAchieving Environmental Sustainability (MDG7) in Nigeria: Progress so Far, Challenges and ProspectsGeomorphological Changes of the Rosetta Mouth, Nile Delta Coast, Egypt during 20th CenturyWaste Control Strategies for Healthy Environment: A Case Study of Female Student HostelsThe Impact of Environmental Pollution in Imo State: A Case Study of Okigwe Local Government AreaThe Earth as a Resource for Art and CreativityIntellectual Property and Remote Sensing Data in Light of Realization of Public InterestThe Effect of Health Safety Management in National DevelopmentSpatial Dimension of Drinking Water Deprivation in Urban IndiaRemoval of Heavy Metals Fe3+, Mn2+, Zn2+, Pb2+ and Cd2+ from Wastewater by Using Rice Straw as Low Cost AdsorbentAnalysis of Land Use/ Land Cover Pattern along the River Benue Channel in Adamawa State, NigeriaSustainable Development of Bioenergy from Agricultural Waste